Breeding of the alfalfa plant morphology for quality - Rotili P.; Gnocchi G.; Scotti C.; Kertikova D. (Quality in lucerne and medics for animal production, 2001)
Quality (protein and fiber contents) in alfalfa are mainly influenced by leaf to stem ratio. In order to maximise this ratio at Lodi Institute we have followed different ways: (i) tolerance to early cutting (blue bud stage); (ii) modification of stem morphology towards maximum height and shorter internodes; and (iii) high growth rate associated to a delay of the reproductive phase. Consequently, three plant models have been defined for the different breeding strategies; data from the three approaches to vigour and quality improvement are presented.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)